Low-Grade Oligodendroglioma of the Pineal Region: Case Report - Lamis, Fabricio Correa; de Paiva Neto, Manoel Antonio; Stavale, João Norberto; Cavalheiro, Sergio (Journal of Neurological Surgery Reports, 2015)
Background Although germ cell tumors and pineal cell tumors account for most of the histologic tumor subtypes, > 17 different tumors can arise in this location. We report a rare case of a low-grade oligodendroglioma that arose in the pineal region.Clinical Presentation A young woman complaining of a headache underwent magnetic resonance imaging that showed a mass in the pineal region and mild hydrocephalus. A ventriculoperitoneal shunt was performed followed by a near-total tumor removal, due to tumor invasion of the tectal plate and thalamus. The histologic examination confirmed the diagnosis of a low-grade oligodendroglioma. The patient then underwent chemotherapy and radiotherapy as adjuvant therapies.Conclusion Although the pineal region is a common place for a large number of tumoral lesions, low-grade oligodendrogliomas are extremely rare in this location. This case is only the second account of a benign oligodendroglioma of the pineal region reported in the literature.
Keywords: oligodendroglioma; pineal region; tectal plate; pineal gland